2004
DOI: 10.1097/01.mcg.0000123204.36471.be
|View full text |Cite
|
Sign up to set email alerts
|

Result of Endoscopic Biliary Drainage in Hilar Cholangiocarcinoma

Abstract: Patients with hilar obstruction usually require bilateral biliary drainage. The prognosis of patients who fail bilateral biliary drainage after contrast injection into both intrahepatic ducts is poor due to a high infection rate in the undrained segments. The incidence of post-endoscopic retrograde cholangiopancreatography cholangitis in those with successful bilateral biliary drainage was less, but still significant. Incomplete subsegmental intrahepatic duct drainage is suggested to be responsible for post-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 19 publications
6
61
3
1
Order By: Relevance
“…Concerns related to performing only unilateral drainage include the inability to relieve jaundice as well as the potential for bacterial contamination of undrained ducts, particularly when a contrast medium is introduced into them (2-6). Supporters of unilateral drainage emphasize the lower complication rate, but caution that overfilling of contrast medium into undrained ducts should be avoided (7)(8)(9)(10). However, preventing overfilling with any certainty seems to be unrealistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns related to performing only unilateral drainage include the inability to relieve jaundice as well as the potential for bacterial contamination of undrained ducts, particularly when a contrast medium is introduced into them (2-6). Supporters of unilateral drainage emphasize the lower complication rate, but caution that overfilling of contrast medium into undrained ducts should be avoided (7)(8)(9)(10). However, preventing overfilling with any certainty seems to be unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…PERCUTANEOUS palliation with metallic endoprostheses is the accepted method to relieve malignant biliary hilar obstruction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Although the necessity of complete biliary drainage remains controversial, it seems certain that drainage of as much of the liver as possible is prudent (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In biliary obstruction in the hepatic hilum, effective drainage is difficult to achieve because of the anatomical complexity of the bile ducts. Various procedures of biliary drainage of hilar biliary obstruction have been performed: percutaneous or endoscopic routes [1][2][3][4][5] , plastic or metallic stents [6][7][8][9][10][11] , and unilateral or bilateral hepatic duct drainage [11][12][13][14][15][16][17][18][19][20][21] . However, no consensus has been reached on the optimal drainage strategy for treating biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the post-procedural morbidity rate of percutaneous techniques is lower compared to the endoscopic technique [9]. PTBD is a direct approach for bile duct decompression in patient with HC and it is usually the procedure of choice in most groups due to effectiveness in decreasing serum bilirubin with low rates of cholangitis [9,10]. In particular, success rate of bile duct decompression is significantly higher by percutaneous approach than EBD in locally advanced HC [11].…”
Section: Drainage Techniquesmentioning
confidence: 99%
“…Moreover, after the procedure, evaluation of tumor length and extension may be less accurate in the presence of one or more stents and for local inflammation and fibrosis [8,9]. EBD is affected by an higher rate of postprocedural complications compared to other techniques, with an overall 25-50% morbidity and 3-5% mortality rate [9,10].…”
Section: Drainage Techniquesmentioning
confidence: 99%